(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background Health sector plays important role in health promotion for older population (HP4OP). The institutions involved constitute a very differentiated sphere: variety of models, structures, financing methods, different forms of providers and payers. HP4OP requires engagement of health sector and medical/public health professionals. Methods Literature review was used: systematic reviews for English-language papers on HP4OP and sectorial institutions activities (incl.PubMed and the healthPROelderly database). Questionnaires, individual interviews and templates were provided for collecting information from country experts. Due to the low feedback for template distribution personal interviews and desk research methods were used. Results Health sector institutions have been indicated and analysed proving the importance of primary care role, institutional and inter-sectorial cooperation, specifically with local governments and NGOs. The important results showed that the medical professional’s approach has to be changed. Moreover, innovations, new technologies used by professionals and patients may significantly improve activities of health sector oriented on effective and long lasting HP4OP. Conclusions: The research performed provided a set of information for the description of the sectorial role in HP4OP, including barriers and limitations, the prerequisites for the cooperation, good practices regarding health promotion projects/ programs focused on old population. The paper, based on EU project, presents the overall picture of health sector involvement in HP4OP and the statement that various institutional arrangements in EU do not contravene the idea of good practices applicability and importance for the effective implementation of HP4OP programs.